What is the Diagnostic Performance of 18F-FDG-PET/ MRI in the Detection of Bone Metastasis in Patients with Breast Cancer? - Filiz Çelebi (European Journal of Breast Health, 2019)

(untitled)
Objective: To evaluate the diagnostic performance of 18F-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/magnetic resonance imaging (MRI) in the detection of bone metastasis in patients with breast cancer.Materials and methods: From August 2018 to January 2019, a total of 23 patients with pathologically confirmed invasive breast cancer underwent whole-body hybrid 18F-FDG -PET/MRI for initial staging and follow-up of their malignancies. The number of the bone metastasis was recorded for each patient. The total 18F-FDG-PET/MRI protocol was compared with PET only and the contrast enhanced fused (CE) component for the detection of bone metastasis.Results: Eight (26%) of 23 patients had bone metastasis. Bone metastases were dominantly localized in the spine (63%) and pelvis (25%). In terms of the total number of detected bone metastasis, there was a statistically significant difference between 18F-FDG-PET/MRI (mean 3.57; median 0; range, 0-2) and PET only component (mean 2.87; median 0; range, 0-1) (p=0.026), but no statistically significant difference was detected between 18F-FDG-PET/MRI and whole-body CE MRI (mean 3.43; median 0; range 0-2) (p=0.083).Conclusion: Whole-body hybrid 18F-FDG-PET/MRI is superior to PET component only, but no statistically significant difference between hybrid 18F-FDG-PET/MRI and whole-body CE MRI is found for the detection of bone metastasis in patients with breast cancer.